TESTS IN INDONESIA AND LITERACY SERVICES AS A FORM OF ENTREPRENEURSHIP IN THE FIELD OF LANGUAGE EDUCATION - Hutkem Repelina; Khairun Nisa; Jamaluddin Nasution; Kudratov Laziz Farkhodovich (JELT : Journal of English Education, Teaching and Literature, 2025)
The growing need for literacy and language competency evaluation in Indonesia has opened up new entrepreneurial opportunities in language and literature education, particularly in exam/test preparation and literacy services. This study aims to describe the forms, potential, and challenges of entrepreneurship arising from these services, and to analyze their contribution to improving the quality of Indonesian language learning. A qualitative descriptive approach was used to explore entrepreneurial practices in the provision of question banks, the creation of assessment instruments, editing and translation services, the development of literacy modules, and writing assistance. Data were collected through interviews, observations, and document studies with business actors, educators, and service users. The results indicate that entrepreneurship in the field of tests and literacy services has high prospects due to the increasing demand for authentic assessments, academic literacy, and writing support in schools and universities. However, challenges arise in aspects of instrument standardization, professional competence of practitioners, and regulations related to academic integrity. This study concludes that entrepreneurship in language and literature education has the potential to become a sustainable creative industry ecosystem for education if supported by capacity building, technology utilization, and collaboration with educational institutions.